Factors associated with early long-acting reversible contraceptives discontinuation in Ethiopia: evidence from the 2016 Ethiopian demographic and health survey - Gedefaw Abeje Fekadu; Akinyinka O. Omigbodun; Olumuyiwa A. Roberts; Alemayehu Worku Yalew (BMC, 2020)
Abstract Background Ethiopia is struggling to achieve the 2020 family planning target. But the current contraceptive prevalence uptake is low and dominated by short-acting methods. Contraceptive discontinuation rate is also high. This analysis was done to identify the reasons and factors associated with long-acting and reversible contraceptives (LARC) discontinuation in Ethiopia. Methods The unit of analysis was LARC-use episodes in the 5 years preceding the survey, generated from the 2016 Ethiopian Demographic and Health Survey data. A total of 1385 LARC episodes were included. Data analysis was done using STATA 15. The event file generated from the contraceptive calendar was merged to the original data set to identify factors associated with LARC discontinuation. Univariate, bivariate and inferential analyses were done for 12 months LARC discontinuation. Result Approximately 82% of LARC episodes were implants. About 45% of intrauterine device (IUD) and 61% of implant episodes were discontinued by 36 months. Side effects and the desire to become pregnant were the main reasons for discontinuation. Women aged 25-34 (HR = 0.26; 95% CI: 0.20-0.35) and those aged 35-49 (HR = 0.17; 95%CI: 0.11-0.26), women who participated in decision-making partially (HR = 0.53; 95%CI: 0.37-0.78), or fully (HR = 0.55; 95%CI: 0.40-0.74) and primiparous women (HR = 0.53, 95%CI: 0.33-0.86) had a lower hazard of discontinuing LARCs. On the other hand, women who had only primary education (HR = 1.32; 95%CI: 1.02-1.72) and women who were not sure about their fertility intention (HR = 2.11; 95%C: 1.28-3.46) had a higher likelihood of discontinuing these methods. Conclusion Majority of LARC episodes were discontinued early, mainly due to the desire for pregnancy or experience of side effects. Older women, particularly those involved in household decision-making, and primipara were less likely to discontinue LARC. Women with only primary education and those uncertain about their fertility intention had a higher likelihood of discontinuation. Family planning service providers should focus on fertility intention and side effects when counseling women for contraceptive choice. Improving women's participation in household decision-making may decrease LARC discontinuation in Ethiopia.